DO-RA: Data-oriented runtime attestation for IoT devices. Issue 97 (October 2020) - Kuang, Boyu; Fu, Anmin; Zhou, Lu; Susilo, Willy; Zhang, Yuqing
Abstract: Remote attestation is an excellent approach to confirm the security states of Internet of Things (IoT) devices. It allows an entity ( verifier ) to validate the integrity of a potentially compromised platform ( prover ). Most of the current attestation schemes are static, which verify only the software integrity of devices. Recently, some runtime attestation schemes based on the Control Flow Graph (CFG) of the program have been proposed to collect the runtime information. However, the algorithm for constructing CFG only focuses on the rationality of the programs' control flow, and ignores the possibility that attackers could compromise the control flow of the device by modifying key data. Some mitigation of runtime exploitation technologies take into account the Unique Code Target (UCT) property of control flow, but there are limitations to their algorithms abilities to find out the constraining data. In this paper, we present a Data-Oriented Control Flow Graph (DO-CFG) that can match a single legitimate target for each control-flow transfer, which guarantees both the rationality and the full uniqueness of programs' control flow. Furthermore, we propose a Data-Oriented Runtime Attestation (DO-RA) scheme based on DO-CFG. It collects some critical non-control data to enhance the detection ability of the attestation scheme, which further ensures the uniqueness of the control flow. We also present a detailed proof-of-concept implementation and analyze our protocol based on Raspberry Pi. We simulate several real applications to evaluate the security and performance of DO-RA, which demonstrates that our scheme provides a more comprehensive detection capability within an acceptable overhead.